Bridging the gap: family resilience as a mediator between parental psychological resilience and care competence in premature infant transitions - Chengxi Zeng; Jianlin Ji; Hanlin Yang; Liling Yang; Yan Jiang; Ping Tang; Qunfeng Lu (BMC Psychology)
Abstract Background High levels of parental infant care competence could facilitate the transition of preterm infants from hospital to home and reduce their readmission rate and emergency visits after discharge. Researchers have confirmed psychological resilience and family resilience were excellent psychological resources that played important roles in the development of parental infant care competence. However, the interaction between these three variables in the parents of preterm infants remains unclear and requires further validation. This study aimed to explore the association between parental psychological resilience and premature infant care competence and the mediating role of family resilience on this relationship. Methods A multi-center cross-sectional study recruited a convenience sample of 381 parents of premature infants across four public hospitals in East China between November 2022 and December 2023. Research instruments included Connor-Davidson Resilience Scale, Family Hardiness Index, and Premature Infant Care Competency Scale. Structure equation modeling (SEM) were used to detect mediating effect of family resilience, while controlling for covariates. Results The average score of parental premature infant care competence was 134.02 points. Differences in levels of premature infant care competence were found across parental gender, education levels and pre-existing diseases. The results of SEM showed a direct relationship between the mentioned three covariates and transitional parental premature infant care competence, but not with family resilience. SEM also revealed psychological resilience as a significant predictor of transitional parental care competence, exerting both direct effects (β = 0.318, P < 0.001, 95%CI: [0.166, 0.464]) and indirect effects (β = 0.111, P = 0.001, 95%CI: [0.049, 0.183]) mediated through family resilience. Conclusions The findings suggested higher psychological resilience related to better family resilience which can provide supportive environment, thus contributing to increased parental premature infant care competence. Future researchers could pay more attention to the early resilience assessment of parents and family resilience improvements based on the formation of therapeutic alliance with the entire family system of preterm babies.